Analisa Pengaruh Pelatihan Online Pemanfaatan Google Classroom bagi Tenaga Pendidik di SMPN 3 Tampaksiring - Ayu Manik Dirgayusari; I Kadek Dwi Gandika Supartha; Aniek Suryanti Kusuma; Welda; Desak Made Dwi Utami Putra (Jurnal Abdi Nusa, 2022)
SMP Negeri 3 Tampaksiring is one of the State Junior High Schools in Gianyar Regency that wants to prepare its educators to be ready to learn online due to the current pandemic conditions. Not all educators at SMPN 3 Tampaksiring can use and operate Google Classroom due to age and unfamiliarity. The purpose of this community service is so that every educator can share subject materials, assignments and exams in one application that can accommodate all of that. Through this community service activity, SMPN 3 Tampaksiring in collaboration with the Indonesian Institute of Business and Technology (INSTIKI) held online training on the use of Google Classroom for educators. This training is conducted online using the Zoom Meeting application. So, it is hoped that all educators at SMPN 3 Tampaksiring can participate and gain an understanding of the use of Google Classroom. Seeing the enthusiasm of the educators, it is possible that similar activities will be continued with other trainings to support teaching and learning activities at the school.